Low-cost virtual presence platform for people with severe motor disability - M. Flores-Calero; M. Torres-Torriti; F. Retamales-Ortega; F. Rosas-Díaz (Revista Iberoamericana de Automática e Informática Industrial RIAI)
Due to a lack of autonomy and diculty in social interactions, people with physical disabilities generally suer from a diminished quality of life. The following document describes the development of a low-cost mobile platform capable of assisting people with severe motor disabilities on independent social interactions.Platform requires a wireless mobile base; adapting two interaction devices, a camera and an eye tracker; and developing a software to integrate all components for an easy-to-use application. Then, in order to validate the operation of the platform, several tests were carried out, using a usability measurement methodology, with different users within a certain age range, with and without disabilities. Consequently, as a first instance of validation, the low-cost platform fulfills the expected function of social interaction assistance for people with disabilities. Finally, as it is an open design and its functioning has been verified, all the necessary information for the construction of the device is freely accessible through the project’s electronic page.